Development of a web-based worksheet with a project-based learning model assisted by GeoGebra - Muchlis, Effie Efrida; Priatna, Nanang; Dahlan, Jarnawi Afgani (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2021)
Previous studies on the use of GeoGebra in mathematics learning were more focused on implementation and effectiveness in learning outcomes. However, not many studies focus on providing opportunities to students to explore GeoGebra to find concepts in plane geometry through developing an application. Therefore, this research and development applied a 4D model to produce a web-based worksheet using project-based learning (PjBL) assisted by GeoGebra that was valid, practical, and effective in the plane geometry course. The web-based worksheet intended to facilitate students to be independent, creative, and able to find the concepts in the plane geometry course through exploration activities using GeoGebra. The results of the data analysis revealed that this research and development produced a web-based worksheet using PjBL assisted by GeoGebra that was valid, practical, and effective. The validity of the web-based student worksheet was shown from the validation results explaining that the worksheet was good in terms of content, construction, and language. The practicality of the worksheet was shown from the results of practitioner assessments and student questionnaires, showing that the web-based worksheet was easy to use and attractive. The effectiveness of the worksheet was shown from the formative assessment results with the interpretation that the use of the web-based worksheet could help students understand the content of plane geometry well.